Improved Postoperative Metrics with Modified Myofascial Closure in Fetal Myelomeningocele Repair. Issue 2 (21st June 2019) - Flanders, Tracy M; Madsen, Peter J; Pisapia, Jared M; Hudgins, Eric D; Mackell, Catherine M; Alexander, Erin E; Moldenhauer, Julie S; Zarnow, Deborah M; Flake, Alan W; Adzick, N Scott; Heuer, Gregory G
Abstract: BACKGROUND: The effect of modifications in fetal myelomeningocele (fMMC) closure techniques has not been extensively studied. OBJECTIVE: To study the effect of a modified closure technique on fMMC postnatal patient outcomes: hydrocephalus, hindbrain herniation, and cyst development. METHODS: We performed single-center retrospective study of a subset of post-MOMS (Management of Myelomeningocele Study) trial patients who underwent fMMC closure. After January 2015, the fetal myofascial closure technique was modified. Needlepoint monopolar cautery was used to raise dural lined myofascial flaps to create a more robust closure. Outcomes between the pre- and postmodification groups were compared with regard to hindbrain herniation, hydrocephalus, and cyst development. Families who transitioned care to local institutions were contacted via telephone for outcome information. RESULTS: From January 2011 to May 2016, data were reviewed from 119 fMMC closure patients. Patients without full follow-up data were excluded from the final analysis. Cerebrospinal fluid diversion was seen in 32 of 74 patients with the standard technique compared to 14 of 45 with the modified closure and was significantly decreased in postmodification when compared to that of the MOMS trial ( P = .01). Hindbrain herniation resolution was significantly decreased in both the pre- and postmodification groups compared to that of the MOMS trial ( P < .01). Prior to January 2015 with standard closure, 23 cysts required resection whereas no cysts required resection in the modified repair group ( P < .01). CONCLUSION: Modified myofascial closure for fMMC closure is safe and feasible. The new approach reflects a decreased rate of cyst development requiring surgical resection, and a trend for improved rates of hindbrain herniation and hydrocephalus.